From stream flows to pollination webs: Exploring the role of riparian environments in plant-pollinator interactions - Cassandre Murail; Irene Villalta; Sabine Greulich; Benoît Geslin; Nicolas Legay; Mathilde Baude (Agriculture, Ecosystems & Environment, 2026)

From species to landscape: Quantification of nectar and pollen reveals seasonal gaps for pollinators in intensive arable systems - Alban Langlois; Alice Michelot-Antalik; Axelle Marchant; Thomas Griat; Ella Soderberg; Chloé Swiderski; Mathilde Baude (Agriculture, Ecosystems & Environment, 2026)

Agricultural practices in olive groves modify weeds floral traits and resources throughout the year - Léa Genty; Aurélie Metay; Elena Kazakou; Mathilde Baude; Antoine Gardarin; Alice Michelot-Antalik; Karim Barkaoui (Agriculture, Ecosystems & Environment, 2025)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.